Corporate Social Responsibility (CSR) and Socio-Economic Change of Post-Reclamation Community in South Wenang Urban Village, Manado City - Kerebungu, Ferdinand; Fathimah, Siti (Universitas Negeri Semarang, 2022)
The reclamation of the beach in Manado city developed as a functional area resulted in a change in the face of the city in coastal areas. As a large company and taking up public space, it must give social responsibility to the community who are deprived of their area of social activity. The purpose of this paper is to review whether CSR programs have been implemented by the developer to communities affected by coastal reclamation and whether socio-economic changes have occurred in the community after coastal reclamation. This study uses a qualitative approach with data collection techniques through observation, interview, and documentation studies. The research found that CSR programs have not been implemented by developers, and there are significant socioeconomic changes among the fishing families after the reclamation taking place in the village of South Wenang. There is a change in the source of livelihood from fishermen to the informal sector (among others food stalls, selling pulses, stalls, retail gasoline sales, parking lots, construction workers). But from the change of livelihood source to the informal sector, the life of the fishing family has not improved significantly.